Tooth Microwear Texture in the Eastern Atlantic Harbour Seals (Phoca vitulina vitulina) of the German Wadden Sea and Its Implications for Long Term Dietary and Ecosystem Changes - Bethune, Elehna; Schulz-Kornas, Ellen; Lehnert, Kristina; Siebert, Ursula; Kaiser, Thomas M. (Frontiers in Ecology and Evolution, 2021)
Marine mammals are increasingly threatened in their habitat by various anthropogenic impacts. This is particularly evident in prey abundance. Understanding the dietary strategies of marine mammal populations can help predict implications for their future health status as well as essential for their conservation. In this study we provide a striking example of a new dietary proxy in pinnipeds to document marine mammal diets using a dental record. In this novel approach, we used a combination of 48 parameters to quantify dental microwear texture (DMTA) as a dietary proxy of feeding behaviour in harbour seals. This method is an established approach to assess diets in terrestrial mammals, but has not yet been applied to pinnipeds. Our aim was to establish a workflow, opening DMTA to pinnipeds by investigating inter- and intra-individual variations. We analysed the upper dentitions of 78 Atlantic harbour seals (Phoca vitulina vitulina).The specimens were collected in 1988 at the coast of the North Sea (Wadden Sea, Germany) and are curated by the Zoological Institute of Kiel University, Germany. An increasing surface texture roughness from frontal to distal teeth was found and related to different prey processing biomechanics. Ten and five year old individuals were similar in their texture roughness with the exception of distal teeth, whereas males and females were similar to each other with the exception of their frontal dentition. Fall and summer specimens also featured no difference in texture roughness. We established the second and third postcanine teeth as reference tooth positions, as those were unaffected by age, sex or season. In summary, applying indirect dietary proxies, such as DMTA, will allow reconstructing dietary traits of pinnipeds using existing skeletal collection material. Combining DMTA with time series analyses is a very promising approach to track health status in pinniped populations over the last decades. This approach opens new research avenues and could help detect dietary shifts in marine environments in the past and the future.